Answer:
Option B - Vertical asymptote: x = 1, horizontal asymptote: y = 0
Explanation:
Given : Function
![(x^2+x-6)/(x^3-1)](https://img.qammunity.org/2019/formulas/mathematics/college/ftktne3lp3kp2vki7gqpe7mizel63m7v9p.png)
To find : What are the vertical and horizontal asymptotes for the function ?
Solution :
Function
![(x^2+x-6)/(x^3-1)](https://img.qammunity.org/2019/formulas/mathematics/college/ftktne3lp3kp2vki7gqpe7mizel63m7v9p.png)
For vertical asymptote,
We equate the denominator to zero,
![x^3-1=0](https://img.qammunity.org/2019/formulas/mathematics/college/bb0kiw7sz3ckbqcylnu2b58vciolokrv74.png)
![\Rightarrow x^3=1](https://img.qammunity.org/2019/formulas/mathematics/college/3g3hvd99wwjbnsq8ux01dnpk2bftwy5wdx.png)
![\Rightarrow x=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/gwc4p9ojilnhv5db3vj9enrpe22502f8p3.png)
So, x=1 is the vertical asymptote.
For horizontal asymptote,
We compare the degree of numerator and denominator.
Degree of numerator is 2 and degree of denominator is 3.
When degree of denominator is greater than degree of numerator then y=0 is the horizontal asymptote.
So, y=0 is the horizontal asymptote.
Therefore, Option B is correct.